From Routine to Crisis: The Impact of COVID‐19 Pandemic on Antibiotic Consumption in Iran - Satar Rezaei; Mohammad Bazyar; Sina Ahmadi; Abdolvahed Khodamoradi (Health Science Reports)
ABSTRACT Background and Aims The COVID‐19 pandemic has significantly impacted the healthcare sector, influencing patients, providers, and the overall system. This study evaluates how the pandemic affected antibiotic prescriptions among 44 million Iranians insured by the Social Security Organization (SSO). Methods In this quasi‐experimental study, we utilized monthly aggregated data on antibiotic prescriptions per 1000 individuals insured by the SSO. We employed a single‐group interrupted time series analysis (ITSA) over a period of 72 months, from March 20, 2016 to February 19, 2020 for the pre‐pandemic phase, and from February 20, 2020 to March 20, 2022, for the during‐pandemic period. Additionally, we conducted a multiple‐group ITSA to assess the differential impact of the pandemic on antibiotic consumption between the direct (SSO‐owned medical centers) and indirect (other private or public centers contracted by the SSO) sectors. Results The study revealed a 30% reduction in the monthly average antibiotic consumption rate when comparing the during‐pandemic period to pre‐pandemic usage across the total sector. The results from the single‐group ITSA indicated that the mean antibiotic consumption per 1000 individuals at baseline was 1664. Following the onset of the pandemic, there was a significant reduction in antibiotic prescriptions, dropping to 484 per 1000 individuals (p ≤ 0.001) in the first month. However, during the pandemic period, antibiotic prescriptions exhibited insignificant monthly increases, averaging 10.7 per 1000 insured individuals. The multiple‐group ITSA revealed that both sectors experienced a decline in antibiotic prescriptions after the outbreak of COVID‐19. Notably, the indirect sector demonstrated a greater reduction, with a decrease of 187 prescriptions per 1000 insured individuals in the first month following the pandemic's onset. Conclusions Our study found a significant reduction in antibiotic consumption. Further research is needed to compare antibiotic use between hospitals and outpatient centers, as well as among COVID‐19 and non‐COVID‐19 patients.